184k views
4 votes
I need this answer ASAP

4+[6-(-2)²]/2

show me the steps

User Astasiak
by
5.1k points

1 Answer

0 votes

Answer:

4+[6-(-2)²]/2 = 5

Step-by-step explanation:

Calculate within parenthesis- [6 - (-2)^2] : 2

Calculate exponents- (-2)^4

= 6 - 4

Add and subtract (left to right)- 6-4

=2

what we have so far- =4 + 2/2

Multiply and divide (left to right)- 2/2

= 1

what we have so far- =4+1

Add and subtract (left to right) 4 + 1

=5

So our final answer would be 5.

Hope this helps!

User Maheer Ali
by
5.3k points